EP656 Post-transcriptional regulation of prognostic factor PD-L1 expression by 17β-estradiol via PI3K/Akt signaling pathway in endometroid cancer. (1st November 2019) - Yang, L; Zeng, X; Xi, M
Abstract : Introduction/Background: Endometriod cancer (EC) is identified as one of the estrogen-dependent malignancies in women worldwide. Estrogen-stimulated cellular proliferation remains the conceptual underpinning of estrogen receptor(ER) dependent mechanism in EC development and progression. The immune checkpoint PD-1/PD-L1 plays a major role in immune suppression within the tumor microenvironment. The aim of this study is to evaluate the expression and prognostic function of PD-1 and PD-L1 in EC and to assess the effects of 17β-estradiol (E2) on PD-L1 expression in estrogen-dependent cancer. Methodology: Paraffin sections of EC patients were used for immunohistochemical (IHC) staining using PD-1 and PD-L1 antibodies. All patients were selected for follow-up and prognostic analysis. Real-time quantitative PCR (q-PCR) and Western blot were performed to detect the mRNA and protein levels of PD-L1 after E2 treatment in estrogen-dependent cancer cells. The mechanism was investigated through co-immunoprecipitation, degradation analysis, sucrose gradient centrifugation and polysome analysis. Results: PD-L1 is highly expressed in epithelium of endometrioid adenocarcinoma, accompanying with more PD-1 positive infiltrating lymphocytes in stroma. Highly expressed PD-L1, associated with advanced stage and high-grade differentiation, shortens the disease-free survival (DFS) and affects prognosis of patients with endometrioid adenocarcinoma. High level and unopposed E2 in tumor microenvironment leads to specific combination of membrane ERα and PI3K p85α regulatory subunit, recruiting PIP3 to phosphorylate No. 473 serine of Akt and forming the active type p-Akt. Activation of Akt can stabilize PD-L1 mRNA and increase PD-L1 translation efficiency. Co-culture results shows that up-regulating PD-L1 expression and activating PD-1/PD-L1 pathway leads to inhibition of T cell activity. Conclusion: Our results demonstrate a new role of estrogen in regulation of anti-cancer immunity, implying PD-L1 as a potential therapeutic target or an outcome parameter in anti-estrogen treatment of EC and estrogen- dependent cancer. Disclosure: Nothing to disclose.